Augmented Reality Strategies to Improve Student Spatial Reasoning in Mathematics Classrooms - Isratul Aini; Prana Kusuma Wardani; Muhammad Rosihan (Gema Cendekia Institute, 2026)
This study examines the effectiveness of Augmented Reality (AR) strategies in improving students’ spatial reasoning in mathematics classrooms. Spatial reasoning is essential for understanding geometry, measurement, and three-dimensional concepts, yet many students struggle with abstract and two-dimensional representations. This research addresses this issue by analyzing how AR-based learning environments support spatial visualization, mental rotation, and spatial orientation. A quantitative experimental design with a pre-test and post-test control group model was employed. Participants were secondary-level students who received instruction through either AR-supported activities or conventional teaching methods. The AR intervention used interactive three-dimensional models that enabled direct manipulation of geometric objects in real-world contexts. Data were collected using validated spatial reasoning tests and analyzed through descriptive and inferential statistics. The results show that students in the AR group achieved significantly higher improvements in spatial reasoning compared to those in traditional classrooms. Gains were particularly strong in three-dimensional visualization and spatial transformation tasks. Students also demonstrated higher engagement and sustained attention during AR-based learning. These findings indicate that AR effectively connects abstract mathematical concepts with concrete visual experiences and serves as a valuable instructional tool when integrated with structured learning objectives.